2022
DOI: 10.1111/brv.12856
|View full text |Cite
|
Sign up to set email alerts
|

From fibre to function: are we accurately representing muscle architecture and performance?

Abstract: The size and arrangement of fibres play a determinate role in the kinetic and energetic performance of muscles. Extrapolations between fibre architecture and performance underpin our understanding of how muscles function and how they are adapted to power specific motions within and across species. Here we provide a synopsis of how this 'fibre to function' paradigm has been applied to understand muscle design, performance and adaptation in animals. Our review highlights the widespread application of the fibre t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 333 publications
(330 reference statements)
0
36
0
Order By: Relevance
“…We were curious how consistently we measured fascicle lengths within our sampled muscles. Charles et al ( 2022 ) showed that small sample sizes of fascicle lengths can be poorly representative of architecture, having knock‐on effects for analysis of muscle function; our test partly addresses this concern. Different fascicle lengths throughout each muscle were measured at least three times on the same day by the same individual, following standard approaches (e.g.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…We were curious how consistently we measured fascicle lengths within our sampled muscles. Charles et al ( 2022 ) showed that small sample sizes of fascicle lengths can be poorly representative of architecture, having knock‐on effects for analysis of muscle function; our test partly addresses this concern. Different fascicle lengths throughout each muscle were measured at least three times on the same day by the same individual, following standard approaches (e.g.…”
Section: Methodsmentioning
confidence: 91%
“…Yet musculoskeletal models and simulations, which use such F max data, typically require muscle fascicle length estimates anyway; our PCSA:AA method does not circumvent that limitation. Relationships of muscle mass or PCSA with fascicle lengths in extant saurians are highly variable across muscles and can be variable within muscles (see Bates & Schachner, 2012 ; Bishop, Cuff, et al, 2021 ), so this is a significant challenge (also see Charles et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…muscle fibre length and PCSA). Our novel approach relies on the curation of anatomical data, which we know to be highly variable, especially fibre length which is especially susceptible to error 26 . Additionally, while there is variability across the masses between our two data sets (Supplementary Table 1 ), the similarities in residual values between those derived from mass and from fibre length are encouraging and would in our opinion unlikely be a result of variability in the data.…”
Section: Discussionmentioning
confidence: 99%